2011
DOI: 10.1073/pnas.1106920108
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 13 C dehydroascorbate as an endogenous redox sensor for in vivo metabolic imaging

Abstract: Reduction and oxidation (redox) chemistry is involved in both normal and abnormal cellular function, in processes as diverse as circadian rhythms and neurotransmission. Intracellular redox is maintained by coupled reactions involving NADPH, glutathione (GSH), and vitamin C, as well as their corresponding oxidized counterparts. In addition to functioning as enzyme cofactors, these reducing agents have a critical role in dealing with reactive oxygen species (ROS), the toxic products of oxidative metabolism seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(168 citation statements)
references
References 48 publications
3
159
1
5
Order By: Relevance
“…Increased reduction of 1-13 C-dehydroscorbate to 1-13 C-vitamin C is an indicator of high glutathione concentrations, which can be associated with malignancy. 13 C MRSI with hyperpolarized 1-13 C-dehydroscorbate in a transgenic adenocarcinoma of the mouse prostate model revealed high 1-13 C-vitamin C in the liver, kidney, and prostate tumor (31). Moreover, the rodent brain demonstrated high rates of dehydroscorbate reduction to vitamin C, highlighting the reductive capacity of the brain.…”
Section: Reactive Oxygen Species and Redox Chemistrymentioning
confidence: 98%
“…Increased reduction of 1-13 C-dehydroscorbate to 1-13 C-vitamin C is an indicator of high glutathione concentrations, which can be associated with malignancy. 13 C MRSI with hyperpolarized 1-13 C-dehydroscorbate in a transgenic adenocarcinoma of the mouse prostate model revealed high 1-13 C-vitamin C in the liver, kidney, and prostate tumor (31). Moreover, the rodent brain demonstrated high rates of dehydroscorbate reduction to vitamin C, highlighting the reductive capacity of the brain.…”
Section: Reactive Oxygen Species and Redox Chemistrymentioning
confidence: 98%
“…Hyperpolarized (HP) 13 C magnetic resonance spectroscopy (HP-MR) is an emerging technique which has found application to the study of a variety of physiologic properties, including metabolism [89,90], tissue pH [91,92], redox state [93], necrosis [94], and blood flow [95]. This method has recently been applied to patients with prostate cancer.…”
Section: Hyperpolarized 13 C Spectroscopymentioning
confidence: 99%
“…[2] Recently, it was demonstrated that the concept of hyperpolarization can be extended to MR probes for surveying the chemical status of living systems. [4][5][6][7][8][9][10][11][12] Because carbon atoms are present in almost all chemical probes, and sophisticated 13 C-isotope labeling procedures are available, 13 C-labeled probes could be a choice for designing a hyperpolarized MR probe. In practice, 13 C-carbon dioxide, [10] 13 C-benzoylformic acid, [11] and 13 C-ascorbic acid [12] have been successfully designed as hyperpolarized MR probes to sense pH, H 2 O 2 , and redox status, respectively.…”
Section: Magnetic Resonance Probe Using a Deuteratedmentioning
confidence: 99%